2008
DOI: 10.1111/j.1743-6109.2007.00730.x
|View full text |Cite
|
Sign up to set email alerts
|

Premature Ejaculation and Serum Leptin Level: A Diagnostic Case-Control Study

Abstract: Introduction Premature ejaculation (PE) is regarded as the most common male sexual disorder. To date, there is no accurate and objective diagnostic test for PE. Aim To determine the diagnostic value of serum leptin level for PE. Methods In a case-control design, the serum leptin level of 46 PE patients referred to our outpatient clinic were determined and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 19 publications
2
13
1
Order By: Relevance
“…This finding can be seen in line with Reas et al (2007) who demonstrated that accelerated weight gain occurs mainly during younger adulthood as it represents a critical time period due to ensuant lifestyle changes involving energy expenditure, dietary intake and they inaccurately assume their weight falls into a normal weight range [26] . Finally, the current results affirmed [17,27] .…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…This finding can be seen in line with Reas et al (2007) who demonstrated that accelerated weight gain occurs mainly during younger adulthood as it represents a critical time period due to ensuant lifestyle changes involving energy expenditure, dietary intake and they inaccurately assume their weight falls into a normal weight range [26] . Finally, the current results affirmed [17,27] .…”
Section: Discussionsupporting
confidence: 73%
“…To the best of our knowledge, this study was the first report to demonstrate a significant relation between BMI and serum leptin in the cases as Nikoobakht and his colleagues as they failed to reveal an association between BMI and serum leptin in their studied cases [17] . Recently, Ventus and his colleague (2016) assumed a potential association between BMI and PE [28] .…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Notably, in contrast to their first study, the second study of Atmaca et al [7] reported a high serum leptin concentration in their control males (24.2±3.8 ng/mL). This finding of Atmaca et al [7] also contrasts the findings of Nikoobakht et al [10], who in 46 Iranian men with PE found a normal but higher baseline serum leptin level (8.3±3 ng/mL) than in a control group of 44 men with nephrolithiasis (3.3±1 ng/mL).…”
Section: Discussioncontrasting
confidence: 51%
“…The aim of the current study was to investigate the role of various pharmacokinetic factors (e.g., paroxetine dosage, serum paroxetine level, Cyp2D6 activity) and serum leptin, gonadotrophin, and prolactin levels, all of which had previously been suggested to be related to PE and SSRI-induced ejaculation delay [7,9,10]. In addition, on the basis of the hypothesis of Waldinger et al [11] that the IELT in men with lifelong PE is related to 5-HT 1A and/or 5-HT 2C receptor functioning, we investigated the role of 5-HT 1A receptor gene C(-1019)G polymorphism.…”
Section: Introductionmentioning
confidence: 99%